Perancangan Prototipe Website Sistem Perizinan Karyawan pada Badan Riset dan Inovasi Daerah Provinsi Bali - Putra Kencana, Dwi Satya; Putra Simanjuntak, Jericho; Yangga Wijaya, Henrico; Ari Dewanggha, I Nyoman; Leksonowati, Vera (UNIVERSITAS SERAMBI MEKKAH, 2024)
The licensing process at BRIDA Bali is still done manually by taking a permit form to the human resources division, then filling in the form by hand, then asking for the superior's signature as approval, then submitting it back to the human resources department. When asking for a superior's signature, employees must wait and stand by at the location. This is certainly less efficient and can disrupt employee productivity. In this research, a solution is proposed by designing a prototype or prototype of the BRIDA Bali employee licensing website to make it easier for employees to carry out permits so that they can do it anywhere and at any time. In designing this prototype, researchers used the Design Thinking method. This method has 5 stages/processes that allow us to obtain innovative output, namely Explore, Emphatise, Experiment, Engage, and Evolve. These five stages are needed to align the user's needs and desires with the researcher's ideas.